Environmental Hydraulics, Turbulence and Sediment Transport - Pu, Jaan H. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In the research on environmental hydraulics, its turbulence, and its sediment transport, constant challenges have been faced. The complexity of hydraulic impacts on sediment transport and turbulent flow properties makes research in this area a difficult task. However, due to pressure from climate change and the mounting issue of pollution, environmental flow studies are more crucial than ever. Bedforming within rivers is a complex process that can be influenced by the hydraulics, vegetated field, and various suspended and bedload transports. Changes in flow conditions due to rain and flood can further complicate a hydraulic system. To date, the turbulence, morphologic, and bedforming characteristics of natural environmental flows are still not well understood. This book aims to bring together a collection of state-of-the-art research and technologies to form a useful guide for the related research and engineering communities. It may be useful for authorities, researchers, and environmental, civil, and water engineers to understand the current state-of-the-art practices in environmental flow modelling, measurement, and management. It may also be a good resource for research, post-, or undergraduate students who wish to know about the most up-to-date knowledge in this field.